2011
DOI: 10.3382/japr.2009-00082
|View full text |Cite
|
Sign up to set email alerts
|

Increasing mixer-added fat reduces the electrical energy required for pelleting and improves exogenous enzyme efficacy for broilers

Abstract: Primary Audience: Feed Manufacturers, nutritionists, Researchers SUMMARYThe prices of fat and diet formulations with exogenous enzymes have caused a reduction in the amount of fat added to broiler diets. Although diets may be cheaper to produce, there is potential for nutrient and exogenous enzyme destruction with low inclusions of fat (0.5 to 1%) because of frictional heat and shear forces produced in the pellet die. Additionally, much of the added fat may be applied by using postpellet spray application, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…7 It improves the productivity without affecting the solidness of pellets; it works well for producing extruded animal feed, and having high-level standard of the equipment. 10 Oil has then been known to be one of the best carriers of micronutrients and that it also increases the energy value of the feed. 11 To this end, it serves as the easiest way to add again the lost nutrients and increase the energy level of the feed.…”
Section: Introductionmentioning
confidence: 99%
“…7 It improves the productivity without affecting the solidness of pellets; it works well for producing extruded animal feed, and having high-level standard of the equipment. 10 Oil has then been known to be one of the best carriers of micronutrients and that it also increases the energy value of the feed. 11 To this end, it serves as the easiest way to add again the lost nutrients and increase the energy level of the feed.…”
Section: Introductionmentioning
confidence: 99%
“…After the 3-21d experimental period and subsequent necropsy, significant differences were obtained for LWG (P=0.007), tibia breaking strength (P<0.001), and tibia ash (P<0.0001) among broilers fed the PC and NC formulations. Data from LWG showed that enzymes 2,3,5,6,7,8, and 9 had similar live weight gains to the positive control (P<0.05, Figure 3). When analyzing FCR among treatments with LWG similar to the positive control, there were no multiple comparison differences.…”
Section: Live Bird Performancementioning
confidence: 85%
“…Data was analyzed using one-way analysis of variance using SAS software (11). Significant differences were determined based on α≤0.05.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations